2021
DOI: 10.15243/jdmlm.2021.091.3219
|View full text |Cite
|
Sign up to set email alerts
|

Growth and survivorship of Vetiveria zizanioides in degraded soil by gold-mining in the Peruvian Amazon

Abstract: In the Peruvian Amazon, large area of primary forest have been deforested by Artisanal and small-scale gold mining (ASGM). Vetiveria zizanioides (Poaceae) is considered an excellent plant for the ecological restoration of degraded lands. The present study aimed to analyze the growth and survivorship of V. zizanioides in degraded soils by gold-mining in the Peruvian Amazon (Madre de Dios). The experiment was conducted under greenhouse conditions, and it followed a randomized complete block design with four trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These results indicate that heavy machinery mining may have a considerable negative effect on species diversity [21], because suction pumping mining forest stands harbor on average approximately two times more species than heavy machinery stands. Given that species diversity usually starts near zero with no woody plants, due to the elimination of vegetation cover [39,41,42] and severe soil degradation [20,43,44,54] by goldmining, our results highlight the lower impact of suction pumping mining on landscape structure, which promotes an increase over time as new species become established [79], and facilitates the faster recovery across the landscape [80]. The lower species diversity after mining abandonment may be explained by a higher dominance (IVI > 10, Table 3) or monodominance [30,95] of pioneer species in 0-5-year-old stands, due to higher tolerance of certain species to unfavorable soil conditions [95] generated by goldmining activities in the study area.…”
Section: Recovery Of Agb Tree Diversity and Forest Structurementioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that heavy machinery mining may have a considerable negative effect on species diversity [21], because suction pumping mining forest stands harbor on average approximately two times more species than heavy machinery stands. Given that species diversity usually starts near zero with no woody plants, due to the elimination of vegetation cover [39,41,42] and severe soil degradation [20,43,44,54] by goldmining, our results highlight the lower impact of suction pumping mining on landscape structure, which promotes an increase over time as new species become established [79], and facilitates the faster recovery across the landscape [80]. The lower species diversity after mining abandonment may be explained by a higher dominance (IVI > 10, Table 3) or monodominance [30,95] of pioneer species in 0-5-year-old stands, due to higher tolerance of certain species to unfavorable soil conditions [95] generated by goldmining activities in the study area.…”
Section: Recovery Of Agb Tree Diversity and Forest Structurementioning
confidence: 99%
“…In the Southeastern Peruvian Amazon (Madre de Dios), studies on biomass estimates in natural regeneration after abandonment by mining activities are scarce. Most studies have focused on assessing the species diversity, floristic attributes, species composition [20,40,41], reforestation/rehabilitation experiments of these degraded ecosystems [42][43][44][45][46], and monitoring forest loss due to goldmining [19,26]. These studies showed that the degree of resilience of tree communities after abandonment by mining activities depends on the level of landscape fragmentation [41], stand age [20], and distance from the forest edge [41].…”
Section: Introductionmentioning
confidence: 99%
“…A key nature-based solution to halt and reverse biodiversity loss, mitigate climate change, and provide direct socioeconomic benefits is the restoration of tropical forests through tree planting that promotes ecosystem recovery [ 15 ]. Active restoration methods like direct seeding or nursery-raised seedlings are used when natural regeneration is impossible [ 16 ], with the latter being the most widely used to recover degraded areas by gold mining in Madre de Dios [ [17] , [18] , [19] , [20] ]. Even though passive restoration is possible when the degraded ecosystem has some resilience and no strong biotic or abiotic filters that limit the establishment of natural regeneration [ 16 ].…”
Section: Introductionmentioning
confidence: 99%